Disruption of asxl1 results in myeloproliferative neoplasms in zebrafish - Evisa Gjini; Chang-Bin Jing; Ashley T. Nguyen; Deepak Reyon; Emma Gans; Michiel Kesarsing; Joshua Peterson; Olga Pozdnyakova; Scott J. Rodig; Marc R. Mansour; Keith Joung; A. Thomas Look (The Company of Biologists, 2019)
Somatic loss-of-function mutations of the additional sex combs-like transcriptional regulator 1 (ASXL1) gene are common genetic abnormalities in human myeloid malignancies and induce clonal expansion of mutated hematopoietic stem cells (HSCs). To understand how ASXL1 disruption leads to myeloid cell transformation, we generated asxl1 haploinsufficient and null zebrafish lines using genome-editing technology. Here, we show that homozygous loss of asxl1 leads to apoptosis of newly formed HSCs. Apoptosis occurred via the mitochondrial apoptotic pathway mediated by upregulation of bim and bid. Half of the asxl1+/− zebrafish had myeloproliferative neoplasms (MPNs) by 5 months of age. Heterozygous loss of asxl1 combined with heterozygous loss of tet2 led to a more penetrant MPN phenotype, while heterozygous loss of asxl1 combined with complete loss of tet2 led to acute myeloid leukemia (AML). These findings support the use of asxl1+/− zebrafish as a strategy to identify small-molecule drugs to suppress the growth of asxl1 mutant but not wild-type HSCs in individuals with somatically acquired inactivating mutations of ASXL1.